The Lower Clergy and Popular Culture: Introductory Remarks to a Current Research Project - Bárth, Dániel (Historical Studies on Central Europe, 2021)
The aim of this paper is to examine the role of the Christian lower priesthood in local communities in eighteenth–twentieth century Hungary and Transylvania in cultural transmission. The author intends to map out the complex and changing conditions of the social function, everyday life, and mentality of the priests on the bottom rung of the clerical hierarchy. Particular emphasis is placed on the activity of priests active at the focus points of interaction between elite and popular culture who, starting from the second half of the eighteenth century, often reflected both directly and in a written form on the cultural practices of the population of villages and market towns. The theoretical questions and possible approaches are centered around the complex relations of the priest and the community, their harmonious or conflict-ridden co-existence, questions of sacral economy, stereotypes of the “good priest” and the “bad priest” as shaped from above and from below, the subtleties of “priest-keeping”, the intentions related to preserving traditions and creating new customs, and the different temperaments of priests in relation to these issues.